Impact of Crossword Puzzle Therapy on Cognitive Performance Among Elderly Individuals - Nurhidayah, Ninik; Rachma, Annisa Aulia (Jurnal Keterapian Fisik, 2026)
Background: The elderly experience a decline in cognitive function due to degenerative processes that affect their independence and quality of life. Crossword Puzzle Therapy is one of the non-pharmacological interventions that can stimulate cognitive functions, including memory, concentration, language, and problem-solving. This study aimed to examine the effect of crossword puzzle therapy on cognitive function among older adults at community-based health service posts in Central Java, Indonesia. Methods: This research utilized a pre-experimental design with a one-group pretest–posttest approach. The sample, selected through purposive sampling, consisted of 35 elderly participants who took part in six intervention sessions over a two-week period. Cognitive function was assessed using the Mini-Mental State Examination (MMSE). Data analysis involved the paired sample t-test for comparison, with the Shapiro–Wilk test applied to assess data normality. Results: The findings revealed an increase in the average MMSE score from 24.74 to 26.20 following the intervention. Results of the paired sample t-test yielded a p-value of <0.001 (<0.05), indicating a statistically significant difference between pre- and post-therapy scores. Conclusion: Crossword Puzzle Therapy significantly improves the cognitive function of the elderly and offers an easy, affordable, and enjoyable intervention that can be applied within the community. Crossword Puzzle Therapy can be an intervention option to prevent cognitive decline and for older adults with cognitive impairment.